Implementasi Pembatalan Putusan Arbitrase oleh Pengadilan Negeri : Studi Putusan Nomor 56/Pdt.Sus Arb/2024/PN Kdr (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Arbitral awards are final and binding as stipulated in Article 60 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. However, this finality becomes ambiguous in practice due to the possibility of filing for annulment of the arbitral award with the District Court, as regulated under Article 70 of the same law. This study further analyzes the legal provisions governing the annulment of arbitral awards—despite their final and binding nature—and explores the implications of such annulments through a case study of an existing court decision. The research employs a normative juridical method, using a statutory approach and case analysis of a legally binding court ruling. The findings reveal that the annulment of Arbitral Award No. 1/LPS/PBJP/1/2024 through the Kediri District Court Decision No. 56/Pdt.Sus-Arb/2024/PN Kdr was grounded on suspicions aligning with the conditions set out in Article 70 of Law Number 30 of 1999—namely, that after the LKPP arbitral award was rendered, a document was acknowledged or declared to be falsified and materially decisive, having been concealed by Surya Graha Utama-KSO (the contractor). The annulment of this arbitral award demonstrates that the final and binding nature does not apply in cases where the grounds for annulment are legally substantiated.